Consumer satisfaction in mediating perceived value and price towards revisit repurchase intention moderated by personal selling - Briliantika Zahra; Surya Bintarti; Asral Asral (Junal Ilmu Manajemen, 2023)
Along with the times, many eastern people are accustomed to making bread as a staple food besides rice. This, in turn, makes the bakery business quite developed. Various well-known bakery business brands include BreadTalk. Based on the Top Brand Award, BreadTalk ranks second. BreadTalk offers a variety of attractive products to consumers so they can make repeat purchases. This study aims to examine the relationship between perceived value and price on repurchase intentions through the mediation of consumer satisfaction moderated by personal selling. This research uses quantitative methods. The population in this study are BreadTalk consumers who live in the Bekasi Regency area. The sampling technique in this study was incidental with a sample size of 100 respondents, with research data analysis using the SmartPLS 4.0 program. Based on the results of testing, processing and data analysis that has been carried out previously on Consumer Satisfaction in Mediating Perceived Value and Price Against Repurchase Intentions moderated by Personal Selling (Study on BreadTalk Products in Bekasi Regency) using SmartPLS, it can be concluded as follows the perceived value of Holland Bakery brand products can encourage consumers to make repurchases, prices set on Breadtalk brand products can encourage consumers to make repurchases, the value felt by consumers on Breadtalk brand products causes satisfaction, so it can encourage repurchase, the price set by the manufacturer of the Breadtalk brand product causes satisfaction, so it can encourage repurchase, a high level of consumer satisfaction can encourage consumers to repurchase Breadtalk brand products, the perceived value of consumers on Breadtalk products affects repurchases by moderating personal selling and the price set by the manufacturer for Breadtalk brand products affects repurchases by moderating personal selling.